Utilization of Problem Based Learning Model as an Effort to Improve Vocational High School Students' Learning Outcomes in Islamic Religious Education Learning - Azhar (MADINA : Journal of Islamic Studies, 2024)
Every learning process has the goal of providing cognitive, affective and psychomotor reinforcement to each individual. In its implementation, this goal can be achieved with many interventions, one of which is the use of learning models. One of the relevant learning models is the problem based learning model. This study aims to improve student learning outcomes by implementing the problem based learning model. This study is a classroom action research. The design used is the Kemmis mc Taggart design with four steps, namely planning, action, observation and reflection. The subjects of this study were tenth grade students of vocational high schools. The data for this study were collected using observation and test techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the problem based learning model can improve the learning outcomes of vocational high school students in Islamic religious education learning. This shows that the problem based learning model can be used as an alternative model in Islamic religious education learning.